Perbandingan Perusahaan Perkebunan Sawit Berdasarkan Kinerja Keuangan Periode 2015-2019 - Wahid Muhammad Shodiq (Hasanuddin University, 2021)
Palm oil has a bright prospect in the future, which is indicated by the average growth rate of vegetable oil consumption by 2050 projected at 3.31%. The effort is inseparable from the role and performance of the palm oil sector companies, where one of the assessments is through analysis of financial statements. The purpose of study is determine whether there are changes income statements between years and know the comparison of financial performance at PT ASTRA dan PT SMART. The research sample is the financial statements of the two companies for the period 2015-2019 from the pages of each company. Data analysis is in the form of descriptive and statistical Independent Sample T-tests. The results showed that changes in the income statement of PT SMART were better than PT ASTRA. Different test shows four of the seven variables namely CR, DAR, DER and GPM between the two companies are different.